SAE Technical Paper Series 2004
DOI: 10.4271/2004-01-0645
|View full text |Cite
|
Sign up to set email alerts
|

Clean Engine Vehicle A Natural Gas Driven Euro-4/SULEV with 30% Reduced CO2-Emissions

Abstract: The goal of the Clean Engine Vehicle project (CEV) was the conversion of a gasoline engine to dedicated natural gas operation in order to achieve a significant reduction in C0 2 emissions. The targeted reduction was 30% compared with a gasoline vehicle with similar performance. Along with the reduction in emissions, the second major requirement of the project, however, was compliance of the results with Euro-4 and SULEV emission limits. The project entailed modifications to the engine and the pre-existing mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…flame speed and volumetric efficiency, the conventional CNG engine yields less brake power than that of gasoline. Several experimental studies have shown that gasoline vehicles retrofitted to CNG are subjected to a 15% to 20% loss in total brake horse power while running on natural gas [14,[35][36][37][38][39][40][41]45,47,54,[58][59][60][61]. Many experimental works have been done on the performance analysis of CNG fuelled engines.…”
Section: Lower Power Outputmentioning
confidence: 99%
“…flame speed and volumetric efficiency, the conventional CNG engine yields less brake power than that of gasoline. Several experimental studies have shown that gasoline vehicles retrofitted to CNG are subjected to a 15% to 20% loss in total brake horse power while running on natural gas [14,[35][36][37][38][39][40][41]45,47,54,[58][59][60][61]. Many experimental works have been done on the performance analysis of CNG fuelled engines.…”
Section: Lower Power Outputmentioning
confidence: 99%
“…Nowadays natural gas, which consists primarily of methane, represents a promising alternative energy source in automotive and heavy-duty field, because of the low negative impact on air quality [1]. Nevertheless, emissions of unburned CH 4 (a much more powerful greenhouse gas than CO 2 ) must be reduced by an effective catalytic after-treatment of the exhausts [2].…”
Section: Introductionmentioning
confidence: 99%
“…On a well-to-wheels basis, CNG produce less greenhouse gases as compared to conventional gasoline and diesel vehicles and when used in public transportation can contribute to the improvement of urban air, reduce adverse health effects and social costs of air pollution [99]. In compliance with Euro-4 and SULEV emission limits, CNG operation in small sedan (model year 2000 and a curb weight of 1020 kg) reduced 30% CO 2 emissions compared to gasoline vehicle with similar configuration [100]. Dondero and Goldemberg [101] reported an average reduction of 20% in CO 2 emissions from the conversion of 21 gasoline light vehicles (24% of GMBlazer vehicles, 28% of VW Kombi vehicles and 48% of VW Quantum vehicles) to CNG.…”
Section: The Use Of Compressed Natural Gas Produced From Flared Gas Fmentioning
confidence: 99%